Relationship between placental pathology and neonatal outcomes - Guo, Xiaojun; Wang, Yixiao; Yu, Hong (Frontiers in Pediatrics, 2023)
Objective: To investigate the distribution of placental pathological features and evaluate the relationship between neonatal outcomes and placental pathology. Methods: This was a retrospective study of singleton pregnant women who completed placental pathology. To find the differences in the distribution of acute intrauterine infection/inflammation and maternal placental vascular malperfusion in groups with preterm birth and/or rupture of membranes. The relationship between placental pathology and neonatal gestational age, birth weight Z-score, neonatal respiratory distress syndrome, and neonatal intraventricular hemorrhage was further explored. Results: A total of 990 pregnant women were included in the study, including 651 full-term, 339 preterm, and 79 preterm premature rupture of membranes. The incidence of acute intrauterine infection/inflammation and maternal placental vascular perfusion was 82.0% and 21.9% in full-term pregnant women with intact membranes, 76.9% and 26.5% in preterm pregnant women with intact membranes, 75.8% and 23.1% in pregnant women with intact preterm membranes, and 72.1% and 44.3% in preterm pregnant women with premature rupture of membranes, respectively. In preterm premature rupture of membranes, acute intrauterine infection/inflammation was associated not only with earlier delivery (adjusted gestational age: -4.3, p=0.006) but also with decreased fetal growth (adjusted birth weight Z-score: -2.4, p=0.01). When placental vascular malperfusion and acute intrauterine infection/inflammation cooccur, associations were also observed with early delivery (adjusted gestational age: -2.6, p=0.04) and decreased fetal growth (adjusted birth weight z-score: -1.6, p=0.04). After accounting for covariates, no relationship between neonatal birth weight Z-score and birth gestational age was observed with maternal placental malperfusion alone. Associations between placental lesions and neonatal respiratory distress syndrome and neonatal intraventricular hemorrhage in preterm premature rupture of membranes were also not observed. Conclusion: Although the effect of maternal placental vascular malperfusion alone on neonatal outcomes is not significant, it is a placental lesion with a higher incidence than acute intrauterine infection/inflammation. In preterm premature rupture of membranes, maternal placental vascular malperfusion and acute intrauterine infection/inflammation co-occurrence resulting in younger gestational age and lower birth weight. Placental pathological superposition may be a unique pathological feature that causes disease, which may provide new research ideas for the precise treatment of neonatal diseases.